Navigating the Technological Landscape in Hospitality: Added Values and Entry Barriers of Technologies 4.0 - Albert Fornells Herrera; Agustina Paradela Morgan; Jordi Ficapal Mestres (SAGE Open)
Technological advancements, particularly Technologies 4.0, have become pivotal in reshaping the hospitality industry thanks to a wide range of new opportunities but knowing when, and how their adoption is beneficial to a company is an arduous task. This uncertainty of whether the investment is worth it or not hinders managers in taking the leap into the future, restraining business performance from reaching its maximum potential. This study investigates the synergistic relationship between the integration of Technologies 4.0 and the hospitality sector’s pursuit of enhanced service quality, operational efficiency, and sustainable growth. Drawing upon an extensive literature review and empirical data, this research aims to shed light on the added values that Technologies 4.0 offer to the hospitality sector, as well as the entry barriers that organizations encounter in their pursuit of technological integration.